Tidal Characteristic Analysis Utilizing Radar Tide Gauge in Cirebon Seawater (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2024)
Radar-based tide gauges are one approach in measuring water level offering easier installation and maintenance. Tidal data recording that has been done commonly applies tide staff or pressure tide gauge. In this study, a radar tide gauge was installed at Cirebon port, northern part of Java island, to determine the tidal characteristics in Cirebon seawaters. Water elevation data was recorded every 15 minutes from July 2022 to November 2023. The tidal component is calculated using least squares method while the tidal type is determined using the Formzahl number. The dominant tidal component known consists of semidiurnal component i.e. M2, S2, N2, K2, 2N2; diurnal component, K1, O1, P1, Q1, J1, TAU1; and shallow water component SSA components with a height of 11.98, 5.58, 2.91, 2.11, 1.45, 11.80, 3.89, 6.11, 2.08, 1.56 and 3.11 (in cm), respectively. Tidal type in the study area is mixed type prevailing Semidiurnal. The tidal range is around 0.8-1 m high with high tide conditions at 6.00-9.00 and 18.00 - 21.00, while low tide conditions are within 11.00 - 14.00 and 01.00 - 04.00. Elevation height calculation based on datum is done by combining the tidal components. Tidal measurement data using radar can be an alternative data to support and complement data recorded in Cirebon and may become a consideration for development and other maritime activities.